The Impact of the Economic and Social Shocks (Crises) of the 2000s on Gross Value Added in Central-Eastern Europe - Szendi, Dora (Geographica Pannonica, 2024)
Territorial economic and social disparities remain a major problem for the European Union today, especially in Eastern Europe. The aim of this study is to analyse the impact of the eco- nomic and social shocks of the 2000s (the economic and financial crisis of 2008-09 and the COVID-19 pandemic) on the economies of four Central Eastern European countries (Czech Republic, Slovakia, Poland, Hungary). The study presents county-level differences in gross value added with classical descriptive statistics, inequality indices, convergence analyses and spatial autocorrelation. The results show that the impact of the shocks of the 2000s var- ies across counties, which led to different paths of recovery. Spatial autocorrelation is signif- icant, but patterns remain stable through the period of exogenous shocks.
Keywords: crises; territorial inequality; spatial autocorrelation